Oleanolic Acid Alleviates Cerebral Ischemia/Reperfusion Injury via Regulation of the GSK-3β/HO-1 Signaling Pathway - Kaili Lin; Zhang Zhang; Zhu Zhang; Peili Zhu; Xiaoli Jiang; Ying Wang; Qiudi Deng; Ken Kin Lam Yung; Shiqing Zhang (MDPI AG, 2021)
Oleanolic acid (OA), a bioactive ingredient of Panax ginseng, exhibits neuroprotective pharmacological effects. However, the protective role of OA in cerebral ischemia and involved mechanisms remain unclear. This study attempted to explore the therapeutic effects of OA both in vitro and in vivo. OA attenuated cytotoxicity and overproduction of intracellular reactive oxygen species (ROS) by regulation of glycogen synthase kinase-3β (GSK-3β)/heme oxygenase-1 (HO-1) signal in oxygen-glucose deprivation/reoxygenation (OGD/R)-exposed SH-SY5Y cells. Additionally, OA administration significantly reduced the area of cerebral infarction and the neurological scores in the rat models of cerebral ischemia with middle cerebral artery occlusion (MCAO). The OA administration group showed a higher percentage of Nissl+ and NeuN+ cells, along with lower TUNEL+ ratios in the infarct area of MCAO rats. Moreover, OA administration reduced ROS production while it suppressed the GSK-3β activation and upregulated the HO-1 expression in infarcted tissue. Our results illustrated that OA significantly counteracted cerebral ischemia-mediated injury through antioxidant effects induced by the regulation of the GSK-3β/HO-1 signaling pathway, implicating OA as a promising neuroprotective drug for the therapy of ischemic stroke.